Chloride stress corrosion cracking of a non-standard, 'Borderline' Chromium-Manganese stainless steel – Problems of counterfeits and substandard materials. (September 2021) - Chu, K.H.; Lam, C.C.; Sun, Y.F.; Cristino, V.A.M.; Kwok, C.T.; Pan, H.; Lo, K.H.
Highlights: Cautions for using nonstandard chromium-manganese steels are provided. Phosphorus and sulphur may cause intergranular SCC even in benign environments. In-grain manganese sulphides may cause transgranular SCC in NaCl. The in-air fracture mode is strain-rate dependent. Abstract: Nonstandard chromium-manganese (stainless) steels are gaining popularity nowadays, but data for them are inadequate as the majority of literature is on the 'pedigrees' such as the standard 200 series and 300 series steels. This paper begins with a brief overview of the counterfeit problems of such steels. It then presents the slow-strain-rate test results of a chromium-manganese 'borderline' stainless steel in room-temperature air, 60 °C NaCl and 60 °C distilled water (the lower-bound temperature for chloride stress corrosion cracking in austenitic stainless steels). At low strain rates (10 -6 s −1 ), grain-boundary segregation of phosphorus and sulphur (especially the latter) can cause intergranular cracking in air and in 60 °C distilled water. In 60 °C NaCl, manganese sulphides may serve as the initiation sites of transgranular cracking. Many producers of nonstandard chromium-manganese (stainless) steels lack impurity control technologies, and so users must be vigilant of this issue. The fracture mode of the 'borderline' stainless steel is strain-rate dependent, changing from being mainly intergranular to being transgranular and dimpled as the strain rate goes up. The reason behind this is unclear, but a plausible suggestion is given in this paper.